2016
DOI: 10.1155/2016/7915041
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Insights from the Osteoporosis Research: A Narrative Review of the Literature

Abstract: Purpose. Much of the research on osteoporosis has been generated quantitatively. However, the qualitative osteoporosis literature provides valuable information on patient and clinician experiences and perspectives, informing the design and implementation of health research and healthcare services. To identify knowledge gaps and inform the design of future qualitative research, a narrative review was conducted to consolidate and synthesize the existing insights available within the qualitative osteoporosis rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…14 Bombak and Hanson emphasize the need for balance between presenting osteoporosis as a serious health condition and producing unwarranted anxiety and inactivity among patients when being diagnosed. 20 Similarly, Salter et al argue in their study of older women's experience of osteoporosis screening that screening for osteoporosis and assessment of fracture risk can be understood as a process of biomedicalisation of aging and bone health. They found that women being diagnosed with asymptomatic osteoporosis and thereby informed about the risk of fractures get an illness experience.…”
Section: Discussionmentioning
confidence: 99%
“…14 Bombak and Hanson emphasize the need for balance between presenting osteoporosis as a serious health condition and producing unwarranted anxiety and inactivity among patients when being diagnosed. 20 Similarly, Salter et al argue in their study of older women's experience of osteoporosis screening that screening for osteoporosis and assessment of fracture risk can be understood as a process of biomedicalisation of aging and bone health. They found that women being diagnosed with asymptomatic osteoporosis and thereby informed about the risk of fractures get an illness experience.…”
Section: Discussionmentioning
confidence: 99%
“…Costs for the patient and healthcare system include the time, effort, and expense related to attending appointments and the resources used to screen in clinical settings, to organize and perform tests, and to interpret results [19]. Patients may not always fully understand the meaning of risk assessment results, nor the consequences of an asymptomatic finding that cannot easily be conceptualized [105, 106]. Individuals undergoing screening, and those who perceive their predicted risk for fragility fracture to be high, may experience anxiety and feelings of uncertainty [105, 107].…”
Section: Introductionmentioning
confidence: 99%
“…Research on patients with osteoporosis and decision support has focused on the development and effect of decision aids [ 14 , 15 ]. Studies have shown that decision aids increase patients' knowledge of options for managing osteoporosis and help them clarify their own preferences [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%